Identify Product Defects In The Injection Molding Process: Identifikasi Cacat Produk Pada Proses Injection Molding - Sulung Wibawansyah, Sulung Wibawansyah (Procedia of Engineering and Life Science, 2024)
Injection molding is a method of processing thermoplastic polymer seeds that are inserted into a hopper intoa barrel then the material is pushed by a screw to enter the mold (mold). However, products produced by injectionmolding machines are sometimes still found defects in the product. Common defects include: Short shot, Flash, Sinkmark, Flow mark, Black spot, Warpage and Colour streaks. And the most causative factors are materials that do notcomply with production procedures, lack of checking on the control panel, mold design errors (mold).Keywords - Injection molding; defects; mold